Managing cattle grazing and overstorey cover for the conversion of pine monocultures into mixed Mediterranean woodlands. Issue 2 (8th December 2014) - Osem, Yagil; Fogel, Tom; Moshe, Yossi; Brant, Shlomo; Ward, David
Abstract Question A large proportion (70%) of coniferous forest area in Israel is used for livestock grazing. Recently, the possibility of managing these monospecific plantations to form mixed conifer–broad‐leaved woodlands via natural regeneration processes has been considered. In light of this we pose the question, how does the interaction of cattle grazing and overstorey thinning (hereafter, thinning) affect natural regeneration in east Mediterranean pine plantations? Location Menashe region, Mediterranean Israel (rainfall = 600 mm·yr−1). Methods The experiment was carried out in a mature (50 yr) Pinus brutia plantation. Ten plots (0.25 ha) were selected, representing thinned (five plots, ≈100 trees·ha−1, leaf area index, LAI≈3) and non‐thinned (five plots, ≈230 trees·ha−1, LAI≈6) forest patches. Paired 100‐m2 subplots were positioned within each plot, one of which was fenced to exclude cattle grazing while the other remained available for grazing. Recruitment, growth and shoot water potential of pines and broad‐leaved tree species were measured after 10 yr of grazing exclusion. Results The density of newly emerged (up to 3‐mo‐old) pine seedlings was decreased by thinning but not affected by grazing. However, pine sapling (established seedlings) density and height were increased by thinning and decreased by grazing. Sapling density of the dominant native oak Quercus ithaburensis was reduced by both thinning and grazing. Thinning enhanced the growth of Q. ithaburensis saplings while grazing restricted their height. Grazing and thinning had no significant effect on the total sapling density of broad‐leaved tree species, but grazing restricted their height and reduced species richness. Grazing reduced topsoil water content in non‐thinned plots but had no effect in the thinned plots. Grazing increased the water potential of pine seedlings while thinning reduced it. Both grazing and thinning had no effect on the water potential of mature Pistacia lentiscus shrubs. Conclusions Natural regeneration within east Mediterranean pine plantations is limited by both dense overstorey cover and cattle grazing. While grazing exclusion is necessary for the establishment and early growth of recruits, reintroduction of grazing at later phases may facilitate the development of young forests by controlling competition.